IDENTIFIKASI MAKROFAUNA TANAH DI BAWAH TEGAKAN KELAPA SAWIT (Elaeis guineensis Jacq.) PADA LAHAN GAMBUT - Miftahul Rahmi; Wardati '; Wawan ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aims to identify the type and amount of soil macrofauna, calculate the population density (K) and the relative density (KR) of soil macrofauna with different water level on peat lands under oil palm stands. This research was carried out by observation, sampling for soil macrofauna data was determined by purposive random sampling method which selected the location in accordance with the purpose of research. The samples of the soil were taken in the circle, live path and die path of oil palm with the total area ​​1 m x 1 m in the soil depth until 15 cm which were repeated 3 times to obtain 18 samples. The data of research were calculated and presented on table, then these data were analyzed by descriptive statistic. These results indicated that the type and amount of soil macrofauna on the circle, live path and die path of oil palm in water level of       43 cm were higher than at 60 cm below in the water soil. The population density (K) and the relative density (KR) of soil macrofauna on the circle, live path and die path oil plam at the water level 43 cm below the soil surface had various types and higher amount than at the level 60 cm. Keywords : Soil macrofauna, oil plam, peat lands